Lifestyle in Multiple Myeloma - a longitudinal cohort study protocol. Issue 1 (December 2016) - Heinrich, M.; Fisher, A.; Paton, B.; McCourt, O.; Beeken, R.; Hackshaw, A.; Wardle, J.; Yong, K.
Abstract Background Deterioration in bone health is one of the presenting symptoms of Multiple Myeloma (MM), a cancer of plasma cells. As a consequence of this condition, patients suffer bone pain and bone damage and report cancer-related fatigue, resulting in deterioration in their quality of life. Evidence in patients with solid tumours shows promise for the positive effects of physical activity on quality of life. However, in the case of patients with MM a better understanding of the association between physical fitness and quality of life factors is still required. Therefore, this cohort study aims to objectively and longitudinally assess activity and fitness levels in patients with MM in order to explore their role in bone health, fatigue and quality of life for this patient population. Methods/Design The study is a prospective cohort study of MM patients in remission to assess physical activity, fatigue and bone health. Clinical markers of health, self-reported measures of psychological and physical well-being, and lifestyle behaviours are assessed at baseline, 3, 6 and 12 months. At each time point, patients complete cardiopulmonary exercise testing (CPET) along with a series of objective tests to assess physical fitness (eg accelerometry) and a number of self-report measures. A complementary qualitative study will be carried out in order to explore patients' desire for lifestyle advice and when in their cancer journey they deem such advice to be useful. Discussion This study will be the first to prospectively and longitudinally explore associations between physical fitness and well-being, bone health, and fatigue (along with a number of other physical and clinical outcomes) in a cohort of patients with MM with the use of objective measures. The findings will also help to identify time points within the MM pathway at which physical activity interventions may be introduced for maximum benefit.